2017
DOI: 10.4236/ojog.2017.73029
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Single Low Dose IV Magnesium Sulphate Adjuvant to Ultrasound Guided Transverses Abdominis Plain Block for Control of Postcesarean Pain

Abstract: Objective: The aim of this study is to determine the role of preoperative low dose intravenous MgSO 4 when given adjuvant to ultrasound guided transversus abdominis plane (TAP) block in augmenting postcesarean analgesic effects and reducing opioid requirements during the first 24 hours. Subjects and Methods: In this prospective, randomized double blind study, a total of sixty full term pregnant women were recruited for the study underwent caesarean section. Thirty patients were assigned to MgSO 4 group (A) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…However, Mireskanadari et al [ 21 ] reported lower VAS scores in the intervention group at one, six, and 12 hours ( p < 0.05), but not at 24 hours [ 21 ]. Similarly, Elrahman and Youssry [ 20 ] reported lower VAS scores at six and twelve hours in magnesium patients ( p < 0.05), but not at two or at 24 hours. Two trials, Paech et al [ 11 ] and Helmy et al [ 23 ], measured VAS scores at comparable values to the placebo-control group at several time points.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…However, Mireskanadari et al [ 21 ] reported lower VAS scores in the intervention group at one, six, and 12 hours ( p < 0.05), but not at 24 hours [ 21 ]. Similarly, Elrahman and Youssry [ 20 ] reported lower VAS scores at six and twelve hours in magnesium patients ( p < 0.05), but not at two or at 24 hours. Two trials, Paech et al [ 11 ] and Helmy et al [ 23 ], measured VAS scores at comparable values to the placebo-control group at several time points.…”
Section: Resultsmentioning
confidence: 84%
“…The seven subsequently included trials ( Table 2 ) encompassed a total of 530 patients, 260 of whom received intravenous magnesium sulphate preoperatively. Four trials administered magnesium concurrently with general anaesthesia [ 20 23 ] (240 patients: 110 receiving magnesium sulphate) while the other three were with neuraxial anaesthesia [ 11 , 24 , 25 ] (290 patients: 150 receiving magnesium sulphate).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations